Abuse-related trauma forward medical care in a randomly sampled nationwide population. Issue 43 (October 2016) - Ho, Cheng-Maw; Lee, Chih-Hsin; Wang, Jann-Yuan; Lee, Po-Huang; Lai, Hong-Shiee; Hu, Rey-Heng; Chen, Jin-Shing
Abstract : Abstract: Abuse-related trauma remains a global health issue. However, there is paucity in nationwide reports. We aim to estimate the incidence of abuse-related trauma forward medical care and identify its characteristics and clinical course in Taiwan. Patients with trauma between 2005 and 2007 that occurred 3 months before or after a diagnosis of abuse were identified from a randomly sampled nationwide longitudinal health insurance database of 1 million beneficiaries. The patients' demographic data, injury pattern, and medical resource utilization were measured, stratified by age and sex, and compared using chi-square test. Risk factors of next trauma event were identified using Cox regression analysis. Ninety-three patients (65 females) were identified (mean age, 20.6 ± 16.3 years), including 61.3% under 18 years of age. For the first trauma event, 68 patients (73.1%) visited the emergency room, 63 (67.7%) received intervention, and 14 (15.1%) needed hospital care. Seven (7.5%), all less than 11 years old, had intracranial hemorrhage and required intensive care. Thirty-three (35.5%) left with complications or sequelae, or required rehabilitation, but all survived. Of the 34 victims of sexual abuse, 32 were aged less than 18 years. Men received more mood stabilizers or antipsychotics (50.0% vs 10.7%, P = 0.030) and reeducative psychotherapy (25.0% vs 0, P = 0.044). Risk factors for a next trauma event were injury involving the extremities (hazard ratio [HR]: 5.27 [2.45–11.33]) and use of antibiotics (HR: 4.21 [1.45–12.24]) on the first trauma event. Abuse-related trauma has heterogeneous presentations among subgroups. Clinicians should be alert in providing timely diagnosis and individualized intervention. Abstract : Supplemental Digital Content is available in the text